IMPACT AND BIOLOGICAL CONTROL OF OMMATISSUS LYBICUS DE BERGEVIN (HEMIPTERA: TROPIDUCHIDAE) ON DATE PALM (PHOENIX DACTYLIFERA L.) - AL-ABRI, NASSER (2023)
The dubas bug, Ommatissus lybicus De Bergevin (Hemiptera: Tropiduchidae), is a piercing-sucking insect species of significant economic importance. The insect attacks date palms (Phoenix dactylifera L.), consuming phloem sap and producing large volumes of honeydew on crop leaves. The deposited honeydew on leaves results in dust accumulation and secondary growth of sooty moulds, which are likely to reduce photosynthesis. Both adults and nymphs cause damage to the palms, with the females also causing necrosis to the palm tissue through oviposition. Major efforts are made every year to control this pest in Oman using repeated applications of insecticides on more than twenty thousand acres infested with O. lybicus. Despite these applications, control has been inconsistent and more research are needed to develop more sustainable and environmentally safe control strategies. The aim of this study was to quantify the effects of O. lybicus on date palm growth and to identify and develop biological control measures using native and commercial entomopathogenic fungi. The effect of different infestation levels of O. lybicus on chlorophyll, date palm biomass, and date palm nutritional composition were investigated. Initial infestations of O. lybicus nymphs exceeding 300 nymphs per palm seedling caused a reduction in palm chlorophyll of up to 40% and plant biomass of 29-34%. Ommatissus lybicus populations of more than 600 insects per palm reduced oviposition by females, possibly due to intraspecific competition over resources. Honeydew droplets showed significant association with chlorophyll content or eggs oviposited on the rachis, which suggests that control can be performed at 3-6 nymphs/leaflet. The pest activities affected the palm nutrients Mg, Ca, P, and K. Magnesium content in palms was associated with chlorophyll reduction as O. lybicus density increased. To investigate the abundance, diversity, and distribution of local entomopathogenic fungi (EPF) in Omani soils, a survey was conducted using the Galleria bait method. The obtained EPF with high sporulation and growth rate were further characterized for their optimal temperature, and infection potential against O. lybicus adults was assessed using scanning electron microscopy (SEM). Fungal species known to be biological agents against insects were identified from 46 isolates collected through this survey and belonged to five genera, Metarhizium spp., Beauveria bassiana, Clonostachys spp., Fusarium spp., and Aspergillus spp. along with five entomopathogenic nematode species that were identified as Acrobeloides saeedi, Oscheius tipulae, Pratylenchus goodeyi, Heterorhabditis indica, and Mesorhabditis sp. In vitro, B. bassiana and M. quizhouense were able to grow and sporulate at temperatures between 25°C and 35°C. Clonostachys rosea had rapid growth on O. lybicus adult cuticle and was first seen after 2 hours post inoculation (hpi). Beauveria bassiana was the most effective fungi against O. lybicus adults, with a 93.4% mortality rate within 3 days post inoculation (dpi). To evaluate the efficacy of native and commercial entomopathogenic fungi control of O.lybicus, four native fungal pathogen isolates, Clonostachys rosea, Metarhizium guizhouense and Beauveria bassiana and Metarhizium anisopliae together with three commercial products, Bio-Power B. bassiana, Bio-Catch Verticillium lecanii, and Botanigard 22WP B. bassiana strain GHA were evaluated for their pathogenicity against O. lybicus eggs, nymphs, and adults. The insects were hosted in Petri dishes and palm seedlings. Furthermore, two fungi M. anisopliae and B. bassiana, were evaluated against the O. lybicus adults under different relative humidity treatments. The highest death rate was achieved by B. bassiana with 76.7% mortality at the adult stage of O. lybicus after 2 weeks of inoculation. The best formulated fungi against O. lybicus nymphs and adults was Botanigard 22WP with a 90.8% and 84.2% mortality rate at the 1st and 2nd instars, and 100% mortality rate at the 3rd, 4th, 5th, and adult stages after 7 dpi. Ommatissus lybicus egg hatching was significantly reduced by Botanigard 22WP and C. rosea with 75.8% and 74.7% unhatched eggs, respectively. Ommatissus lybicus adults inoculated with two native fungi B. bassiana and M. anisopliae had a significantly higher mortality rate of 100% when incubated at a relative humidity of 50% and above. This study showed a promising biological control alternative against O. lybicus as part of Integrated Pest Management (IPM).